Verification of the Efficacy of Passive Autocatalytic Recombiners in a Typical Pressurized Water Reactor under a Station Blackout Condition - Daegwang Hong; Donghyun Cho; Jinwoo Kim; Aya Diab; Cigdem Cildag (Science and Technology of Nuclear Installations)
The presence of a stable stratified gas cloud inside the containment near or at the flammability limit may lead to deflagration or even detonation which may challenge the containment and cause a radioactive material release into the environment. To mitigate this risk, a number of approaches have been proposed, for example, containment inerting or venting and use of passive autocatalytic recombiners or igniters. However, for these measures to be effective, a thorough analysis of the hydrogen dispersion and associated phenomena is indispensable during the design phase as well as the mitigation phase during a severe accident. In this work, a MAAP analysis is performed to assess the hydrogen risk in a typical pressurized water reactor (PWR) containment. An extended station blackout (SBO) was chosen as an initiating event given its high contribution to the core damage frequency. RCS depressurization and external injection are mitigation techniques implemented consecutively to extend the coping capability of the plant for the extended SBO scenario. A sensitivity study is performed to select the combination of timing and flow rate that generate the most severe case for the “in-vessel phase of hydrogen generation.” Subsequently, a number of passive autocatalytic recombiners (PARs) were implemented to mitigate the hydrogen risk during the first three days of the accident. The Shapiro diagram is used to assess the flammability condition of the containment atmosphere based on MAAP analysis. The results show that the gas mixture composition is acceptable in the majority of the containment compartments and only marginally acceptable in the cavity. Even under the conservative conditions of the accident, the simulation results confirmed the sufficiency of recombiners alone without igniters in the low hydrogen concentration zones, while for compartments close to the sources, additional mitigation may be needed.